Controlling light-induced dielectric response of Sr/Ni-modified (K0.5Na0.5)NbO3 ceramics by narrow bandgap method. (1st June 2022) - Zhang, Jie; Xu, Jiwen; Yang, Ling; Cao, Zhijie; Yuan, Changlai; Zhou, Changrong; Wang, Hua; Rao, Guanghui
Abstract: The change of dielectric constant at UV-VIS light irradiation was named as photo dielectric response (PDR). High PDR discovered in lead-free semiconducting ferroelectric ceramics will help to develop new types of photoelectric devices. The (1- x )(K0.5 Na0.5 )NbO3 - x Sr(Ni0.5 Nb0.5 )O3-δ (KNN- x SNN) new system was successfully synthesized by solid-phase sintering. The phase structure of KNN- x SNN ceramics gradually evolves from the orthogonal phase to the cubic phase. The size of grains of as-sintered ceramics is reduced to the sub-micron level of 150–180 nm. The bandgap is tuned to ∼1.17 eV. High dielectric tunability in UV-VIS region can be achieved, which shows the tunability of ∼452% at 80 Hz and ∼18.1% at 100 kHz under 365 nm light, and ∼133.2% under 440 nm light in the KNN-0.04SNN ceramic. Meanwhile, the reproducible capacitive switching response under the light off and on state can be observed, which shows a capacitive ratio of about 6. These results indicate that this system has considerable advantages in the development of contactless devices under UV-VIS region.